Pengembangan Media Flipbook Materi Menghidangkan Wine Pada Mata Kuliah Food and Beverage Service & Bar - Euginia Kewa Basablolon; Luh Masdarini; Risa Panti Ariani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aims to develop flipbook-based learning media for the wine serving material in the Food and Beverage Service and Bar course. The research employed a Research and Development (RnD) method using the 4D development model, which consists of the stages of define, design, development, and disseminate. The research subjects included material experts as well as learning media and design experts. Data were collected through observation, interviews, and questionnaires. The results showed that the developed flipbook learning media was categorized as “Very Feasible” for use, with a feasibility score of 86.7% from material experts and 96,7% from media and design experts. Based on these results, the flipbook learning media is considered suitable to be used as a supporting learning medium in the Food and Beverage Service and Bar course.